Analysis of revolting elements in Munowar Rana’s poetry collection "Jangli Phool" - Khizra; Bibi, Maheen; Gull, Kainat (sourcecoder, 2024)
Historical narratives provide profound insights into the thoughts, beliefs, traditions, and customs of ancient civilizations, often conveying wisdom through actions rather than words. This enduring relevance accounts for their persistent popularity across generations. The interaction and mutual influence between different cultures have resulted in shared themes within their literary traditions. For instance, the Brahuis, one of the oldest communities in the world, boast a rich literary heritage of poetry and prose that has gained global recognition. When comparing Brahui stories with those in Urdu, striking similarities become evident, with the primary distinctions lying in language and stylistic expression. While Urdu storytellers emphasize linguistic nuances and expressive elements, Brahui narratives, when translated into Urdu, preserve their original essence. Despite linguistic differences, the principles of storytelling remain consistent across cultures, reflecting a universal approach to narrative structure and thematic content. This commonality underscores the shared human experience that transcends linguistic and cultural boundaries, highlighting the universal nature of storytelling.